Low-dose CT coronary angiography for assessment of coronary artery disease in patients with type 2 diabetes - A cross-sectional study. Issue 1 (December 2015) - Ulimoen, Geir; Ofstad, Anne; Endresen, Knut; Gullestad, Lars; Johansen, Odd; Borthne, Arne
Abstract Background Silent coronary artery disease (CAD) is prevalent in type 2 diabetes mellitus (T2DM). Although coronary computed tomography angiography (CCTA) over recent years has emerged a useful tool for assessing and diagnosing CAD it's role and applicability for patients with T2DM is still unclarified, in particular in asymptomatic patients. We aimed to assess the role of CCTA in detecting and characterizing CAD in patients with T2DM without cardiac symptoms when compared to gold standard invasive coronary angiography (ICA). Methods This was a cross-sectional analysis of patients with T2DM without symptomatic CAD enrolled in the Asker and Baerum Cardiovascular Diabetes Study who, following clinical examination and laboratory assessment, underwent subsequently CCTA and ICA. Results In total 48 Caucasian patients with T2DM (36 men, age 64.0 ± 7.3 years, diabetes duration 14.6 ± 6.4 years, HbA1c 7.4 ± 1.1 %, BMI 29.6 ± 4.3 kg/m2 ) consented to, and underwent, both procedures (CCTA and ICA). The population was at intermediate cardiovascular risk (mean coronary artery calcium score 269, 75 % treated with antihypertensive therapy). ICA identified a prevalence of silent CAD at 17 % whereas CCTA 35 %. CCTA had a high sensitivity (100 %) and a high negative predictive value (100 %) for detection of patients with CAD when compared to ICA, but the positive predictive value was low (47 %). Conclusions Low-dose CCTA is a reliable method for detection and exclusion of significant CAD in T2DM and thus may be a useful tool for the clinicians. However, a low positive predictive value may limit its usefulness as a screening tool for all CAD asymptomatic patients with T2DM. Further studies should assess the applicability for risk assessment beyond the evaluation of the vascular bed.